Integration of a Vehicle Congestion Detection and Alert Prototype in the city of Arequipa. - Flores-Gutierrez, Mateo; Herrera-Ramos, Edwin; Apaza-Cornejo, Mathias; Valeriano-Cuba, Eddu; Juarez-Alvarez, Camila; Esquicha-Tejada, José (LACCEI, 2024)
Previous research has shown that cities present vehicular congestion. This research focuses on the development of a prototype for detecting and warning of traffic congestion using cameras with multiple sensors to identify the number of vehicles present in an area. The population of Arequipa was 87% satisfied with the perception and effectiveness of the proposed prototype. The importance of using technological advances helps to provide solutions to society by providing real-time information on faster alternative routes, based on the number of vehicles present and estimates of arrival time to avoid traffic, and an economic and financial analysis was performed so that municipalities can appreciate the profitability of using this proposal